New Frontiers for Internal Audit Research*. (2nd November 2021) - Christ, Margaret H.; Eulerich, Marc; Krane, Ronja; Wood, David A.
ABSTRACT: Internal audit provides useful and valuable services to organizations, and academic research has established its importance in improving corporate governance. However, the body of internal audit research is still relatively small. Indeed, there are many emerging, lesser‐known topics and practitioners would like guidance. The primary focus of this paper is to make specific recommendations for future research based on surveys, interviews, and discussions with practitioners. We identify three broad areas for additional academic research: innovation in information technology, staffing and personnel development, and agile auditing. In each area, we describe current practices and discuss the relevant accounting literature, noting gaps where additional inquiry is needed. We also provide a list of testable research ideas to help inform academics about practice‐relevant research questions that would not only add to the academic literature, but would benefit practitioners who seek guidance. We hope this paper will inspire more academic research that investigates important internal audit questions. RÉSUMÉ: Nouvelles frontières dans le domaine de la recherche sur l'audit interne L'audit interne fournit des services utiles et précieux aux organismes, et la recherche a mis en lumière son importance pour l'amélioration de la gouvernance d'entreprise. Toutefois, le corpus de recherche sur l'audit interne est encore relativement restreint. En fait, il existe plusieurs thèmes émergents et moins connus sur lesquels les praticiens aimeraient obtenir des orientations. Le but principal de la présente étude est de formuler des recommandations précises pour la recherche à venir, recommandations fondées sur des enquêtes, entrevues et discussions avec des praticiens. Nous cernons trois grands domaines nécessitant davantage de recherche : innovation en technologie de l'information, dotation de personnel et perfectionnement professionnel, et audit agile. Pour chaque domaine, nous décrivons les pratiques actuelles et examinons la littérature comptable pertinente, tout en relevant les lacunes sur lesquelles il est nécessaire de se pencher davantage. Nous dressons aussi une liste des idées de recherche testables afin d'informer les chercheurs des questions de recherche pertinentes pour la pratique qui, non seulement enrichiraient la littérature savante, mais profiteraient également aux praticiens en quête d'orientations. Nous espérons que la présente étude suscitera davantage de recherche portant sur d'importantes questions d'audit interne.